Stabilization of solutions to the initial boundary–value problems for quasilinear parabolic equations - Tedeev, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Lower bounds are obtained for solutions of the initial–boundary Dirichlet problem for high order equations. Sharp bounds are also obtained for ess sup| abla u(x,t)| of the Neumann initial–boundary problem for a second order equation in D=Ω × (t>0), where Ω R^n, n≥ 2 is a domain with noncompact convex boundary.